THE CONSTITUTIVE FUNCTIONS OF SYMBOLIC FORMS OF CULTURE E. CASSIRER - Olena Yatsenko ("Scientific Information Agency "Science-technologies-information" LLC, 2019)
The main instrument of human interaction with the world is called by Cassirer as symbol. It is the ability of a person to create and operate with symbols, that the thinker attributes as a significant feature of the human essence. Character of creation is not representative of human activity in reality, but constitutive. In other words, the person does not reflect the objects and processes of the world in consciousness, and the consciousness itself projects a certain symbolic meaning of reality. The symbol outlines of the procedure for defining an object or phenomenon, and in this its transcendental nature. All symbolic forms differ in their specificity (meaningful, expressive-representational, logical- verbal, etc.), but they all have a similar structure. The structure of the symbolic form is differentiated by the type of connection between speculative and empirical, and includes expression (perception), representation (contemplation), pure meaning (concept). That is, the formation of a corpus of culture occurs as a dialectical process of abstracting information of empirical experience, which in turn is determined by abstract symbolic forms. Indicative in this respect is the postulation that not individual pieces of empiricism are compared, but abstract forms denoting and defining perception. This act occurs at the stage of transformation of perception into imagination.